Spatial Analysis of the Effect of Economic Growth and Unemployment on Poverty in Papua Province and Its New Autonomous Regions - Iis Pebriyanti; Hasan Basri Umar; Yundy Hafizrianda (Review of Multidisciplinary Academic and Practice Studies, 2024)
Purpose: Poverty in Papua Province and its three New Autonomous Regions remains the most critical development challenge in Indonesia, given its persistently high ranking relative to the national average. This study analyzes the effect of economic growth and the open unemployment rate on poverty while accounting for spatial heterogeneity across districts and cities. Methodology: Panel data from 29 districts and cities in Papua, South Papua, Central Papua, and Highland Papua for 2020 to 2024, yielding 145 observations, were analyzed using Geographically Weighted Regression Panel with an adaptive bisquare kernel function, following a Breusch-Pagan test for spatial heterogeneity and a global Ordinary Least Squares benchmark. Results: The Breusch-Pagan test confirmed significant spatial heterogeneity. The Geographically Weighted Regression Panel model substantially outperformed the global model, raising R squared from 35.78 percent to 73.23 percent and lowering the corrected Akaike Information Criterion from 965.00 to 881.87. Locally, economic growth and unemployment negatively affect poverty with varying sensitivity across regions, and unemployment proved a more dominant and spatially stable determinant than growth. Conclusions: Poverty reduction strategies following regional expansion must be spatially differentiated rather than uniform. Limitations: The study covers only five years, three predictors, and one geographic cluster of provinces. Contributions: The study offers one of the first district-level spatial panel analyses of poverty determinants across Papua's newly expanded provinces.